External Trade Bulletin of the Arab Region, Twenty-Fourth Issue - United Nations Economic; Social Commission for Western Asia (United Nations, 2017)
The Bulletin presents data and statistical indicators on external trade in goods of Arab Countries. Data are presented in time series until 2014 and were drawn primarily from national sources, as well as from secondary sources where appropriate. It provides total and detailed data on intraregional and international trade of Arab countries, which are useful to policymakers, analysts and researchers and other users at the national, regional and international levels.